Foundations of Object-Oriented Programming Using .NET 2.0 Patterns - Gross, Christian (Apress : Imprint: Apress, 2006)
Foundations of Object-Oriented Programming Using .NET 2.0 Patterns solves the object-oriented and pattern-programming problem by mixing the two-the book teaches object-oriented concepts using patterns, or a solutions-based approach. The book's material is organized around tasks and patterns, and illustrated through development problems and solutions that include persistence, code efficiency, and good design. This book is of special interest to those who want to learn how to use .NET 2.0 Generics in conjunction with patterns. This unique book is based on the author's lectures, and the information unfolds in a practical manner.